Sex differences in trajectories to cardio-renal and mental health outcomes following the onset of type 2 diabetes: An observational cohort study using multi-state analysis in the UK Clinical Practice Research Datalink - Fabiola Eto; Miriam Samuel; Daniel Stow; Rafael Henkin; Alisha Angdembe; Michael R. Barnes; Sarah Finer; Rohini Mathur (PLOS Medicine, 2026)
Background Type 2 diabetes (T2D) presents a significant global health challenge, and its prevalence is expected to rise. T2D is associated with diverse complications, including cardiovascular diseases (CVD), end-stage renal disease (ESRD), and mental health disorders like depression and anxiety. Previous research has demonstrated sex differences in the metabolic risk profile, clinical characteristics, and care related to T2D and its complications, including mental health conditions. In this study, we aimed to describe the trajectories of hypertension, cardiovascular diseases, ESRD and mental health conditions in women and men from different age groups with T2D. Methods and findings Using individual-level anonymised linked primary and secondary electronic health record (EHR) data from the United Kingdom (UK) Clinical Practice Research Datalink (CPRD) GOLD, we carried out an observational cohort study of 28,720 individuals with incident T2D between 2010 and 2020. We applied competing risk semi-Markov multi-state analysis to investigate and understand the different transitions to cardiovascular disease, ESRD, and mental health conditions following the onset of T2D in women and men. During a median follow-up of 6.8 years, 39% of the cohort moved to another health state. Men constituted 62% of the cohort, with a median age of 54 (IQR 46, 64) at T2D onset, while women were typically older at diagnosis (mean = 56, IQR = 45, 67). Disease trajectories differed significantly by sex: women were more likely than men to be diagnosed with mental health conditions post-T2D, (8.1% versus 5.3%), while men were more likely to be diagnosed with CVD/ESRD (8.4% versus 5.3%) and hypertension (21.1% versus 20.2%) trajectories than women. Women showed higher average of health service utilisation and long-term prescribing than men. Women experienced a later onset of events compared to men. Both women and men who had a combination of T2D and a mental health condition experienced premature mortality compared to other trajectories. Hypertension was the most frequent event following T2D onset across all age groups and sexes. As a study limitation, some of the observed differences in mental health diagnoses between women and men may reflect differences in healthcare-seeking behaviour rather than true differences in the underlying proportions of these conditions. Conclusions Our study highlights sex-specific differences in disease trajectories following T2D onset, emphasising the need for stratified healthcare interventions. Women exhibited greater vulnerability to mental health conditions post-T2D, while men showed higher proportion of cardiovascular and renal complications, and had earlier onset of most events compared to women. Both sexes experienced earlier mortality when T2D was combined with a mental health condition. Current UK medical guidelines lack sex-specific prevention strategies and management for T2D and comorbidities, especially mental health conditions. Our findings draw attention to the importance of tailored management strategies that consider sex, age, and the complex interplay of physical and mental health in T2D care.